EFEKTIVITAS PELAKSANAAN PENAGIHAN PAJAK DI KPP PRATAMA DENPASAR BARAT PADA MASA PANDEMI COVID-19 - I Made Adi Surya Jaya; Supriyadi Supriyadi (JURNAL PAJAK INDONESIA, 2021)
The COVID-19 pandemic has had an impact on Indonesia's economy. This can be seen from the decrease in state cash receipts from the taxation sector. One possible cause is the actions of tax collection that is not maximal. This study aims to determine the effectiveness of tax collection during the COVID-19 Pandemic (March-December 2020). Effectiveness is assessed based on the percentage rate of realization of disbursement of tax receivables resulting from tax collection actions. The analysis method used in this study, namely quantitative and qualitative method by utilizing tax collection data at KPP Pratama Denpasar Barat. The results showed that the percentage rate of effectiveness of tax collection during the COVID-19 pandemic (March-December 2020) in KPP Pratama Denpasar Barat was considered ineffective. The effectiveness rate also decreased significantly compared to the previous two years. The decrease is due to the many obstacles due to the COVID-19 pandemic that KPP Pratama Denpasar Barat must face in carrying out tax collection actions.